2017
DOI: 10.1080/09500693.2017.1310407
|View full text |Cite
|
Sign up to set email alerts
|

Analysing teachers' operations when teaching students: what constitutes scientific theories?

Abstract: The aim of the study is to analyse teachers' efforts to develop secondary school students' knowledge and argumentation skills of what constitutes scientific theories. The analysis is based on Leontiev's three-level structure of activity (activity, action, and operation), as these levels correspond to the questions why, what, and how content is taught. The unit of analysis was a school development project in science education, where design-based interventions were conducted. Data comprised notes and minutes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…This study supports several studies Mona and Clas [26] and Gaikwad [27] that different students have different preferred styles of order of progressing the assimilation of information, further that teachers in secondary schools must consider both the structure of the content, and the order different students prefer to assimilate the content as new knowledge.…”
Section: Preferred Order Of the Processing Of Information In Learningsupporting
confidence: 89%
See 1 more Smart Citation
“…This study supports several studies Mona and Clas [26] and Gaikwad [27] that different students have different preferred styles of order of progressing the assimilation of information, further that teachers in secondary schools must consider both the structure of the content, and the order different students prefer to assimilate the content as new knowledge.…”
Section: Preferred Order Of the Processing Of Information In Learningsupporting
confidence: 89%
“…The researcher wanted to find whether the students of private and public secondary schools in Nairobi County had a different preferred order of progressing the processing of information into knowledge in learning. Univariate analysis of variance of responses from 659 respondents done descriptive statistics (Table 10) revealed that 73.7 % (486) are sequential learners (that is they prefer to gain understanding linearly, with each new piece of information building logically from previous pieces) while 26 53very strong preference for one of the dimensions. Besides, of the total treatment sample 659 the data indicated 25.6% (169) had a balanced preference for two of the dimensions, 58.9% (388) had a moderate preference for two of the dimensions, and 15.5 % (102) had very strong preference to one of the dimensions.…”
Section: Preferred Order Of the Processing Of Information In Learningmentioning
confidence: 99%
“…Students who have argumentation skills can present conclusions based on information or reasons (Holmqvist & Olander, 2017;Kirana, et al, 2018;Lin, et al, 2017;Viyanti, et al, 2016). Hence the "Causality" feature is presented as shown in Figure 2.…”
Section: Figure 1 Science Investigation Featurementioning
confidence: 99%
“…Teacher must understand how language influences learning and develop strategies to enhance students' successful appreciation of appropriate scientific language on the continuum between daily and scientific use (Schleppegrell, 2016). Hattie (2012) implies that research into these areas might occur in a collegial learning environment, leading to the proposal of "design research" agendas (Anderson & Shattuck, 2012) in which schoolbased teachers "own" authentic practice and engage in iterative cycles of planning, enactment, and evaluation of teaching and learning (for examples in genetics and nature of science, see Olander & Holmqvist, 2013;Holmqvist & Olander, 2017). This is not unlike the lessonstudy model commonly used in Japan and frequently practiced elsewhere.…”
Section: The Role Of Language In Biology Instructionmentioning
confidence: 99%